Reverse ballistics penetration of Kevlar® fabric with different indenters at different loading rates. Issue 10 (June 2017) - Guo, Zherui; Zheng, James; Chen, Weinong
In this study, the mechanical load on a bullet-shaped indenter when impacted by a single-ply Kevlar fabric was experimentally investigated using a reverse ballistics method at both quasi-static and dynamic rates. Different indenter geometries, namely the 9-mm Luger, .223 Remington, and .308 Winchester bullet geometries, were used. The penetration load of the stationary indenter was measured using a force transducer located behind the indenter, and the penetration load was then plotted against the impact velocity of the fabric sample. Different mechanisms of penetration were observed at different impact velocities. Penetration mechanisms were also found to be highly dependent on projectile nose geometry. A modified method to obtain an approximate ballistic limit based on the impact loads was used to compare the efficacy of different geometry types.